2016
DOI: 10.1016/j.drugalcdep.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide increase in hospitalizations for heroin-related soft tissue infections: Associations with structural market conditions

Abstract: Introduction Little is known about trends in national rates of injection-related skin and soft tissue infections (SSTI) and their relationship to the structural risk environment for heroin users. Use of Mexican-sourced “Black Tar” heroin, predominant in western US states, may have greater risk for SSTI compared with eastern US powder heroin (Colombian-sourced) due to its association with non-intravenous injection or from possible contamination. Methods Using nationally representative hospital admissions data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 53 publications
(84 reference statements)
2
83
1
Order By: Relevance
“…Information for each de-identified discharge includes age, race, gender, as well as diagnosis and procedure codes. The NIS has been used in many studies to estimate trends in hospitalizations for a variety of medical conditions including but not limited to HCV and mental and substance abuse disorders [17, 19–21]. We applied for and received an exemption from the Tufts Health Sciences Institutional Review Board because the data from NIS are de-identified.…”
Section: Methodsmentioning
confidence: 99%
“…Information for each de-identified discharge includes age, race, gender, as well as diagnosis and procedure codes. The NIS has been used in many studies to estimate trends in hospitalizations for a variety of medical conditions including but not limited to HCV and mental and substance abuse disorders [17, 19–21]. We applied for and received an exemption from the Tufts Health Sciences Institutional Review Board because the data from NIS are de-identified.…”
Section: Methodsmentioning
confidence: 99%
“…Other drug injection injuries and infections, e.g. SSTI, endocarditis and hepatitis C, are also on the rise in the US (Larney et al 2017, Zibbell et al 2015, Ciccarone et al 2016). …”
Section: A Crisis Of Historic Scalementioning
confidence: 99%
“…PWID present for medical care more often than the general population (Kerr et al, 2005; Stein et al, 1993) and in the U.S., are more likely to be uninsured, which may indicate lower access to health care (Tookes et al, 2015). Of particular concern, inpatient hospitalization rates of opiate-related SSTIs in the U.S. have grown substantially, with a recent study showing a doubling of these rates from 1993 to 2010 (Ciccarone et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Repeatedly injecting black tar intravenously can lead to necrosis, vascular collapse, and sclerosis, thus encouraging alternative injection methods that are risky for SSTIs (e.g., intramuscular injection; Dunbar & Harruff, 2007). Furthermore, recent data shows that cities where black tar is the dominant form of heroin (compared to powder forms) have higher rates of hospitalization for SSTIs (Ciccarone et al, 2016). …”
Section: Introductionmentioning
confidence: 99%